The Effectiveness and Safety of Botulinum Toxin Injections for the Treatment of Congenital Muscular Torticollis. Issue 8 (November 2020) - Qiu, Xin; Cui, Zhiwen; Tang, Gen; Deng, Hansheng; Xiong, Zhu; Han, Shuai; Tang, Shengping
Abstract : Objective: Botulinum toxin have been used to treat congenital muscular torticollis for the last 25 years; however, few studies have been published with only limited cases and short-term follow-up. The aim of the present study is to systematically review the effectiveness and safety of botulinum toxin injections for congenital muscular torticollis by analyzing these relevant literatures. Methods: The authors searched PubMed, Web of Science, EMBASE, Cochrane Library, China Biology Medicine, for all articles about botulinum toxin injections for the congenital muscular torticollis. The MINORS evaluation tool was adopted to evaluate the quality of these studies. Meta-analysis calculations are made by R software 3.6.2. Results: This study search involved strict inclusion criteria and targeted data collection. Ten studies were included, with a total of 411 patients, comprising 1 non-randomized experimental study and 9 cases or case series. The results of our meta-analysis of single rate showed that the overall effective rate of botulinum toxin for congenital muscular torticollis was 84% (95% confidence interval [CI] 67%–96%). After botulinum toxin treatment, the conversion rate to surgery was 9% (95% CI 4%–22%), and the adverse reaction rate was 1% (95% CI 0%–3%). The most common adverse reactions among these included studies involve injection site erythema and transient dysphagia. Conclusion: Current evidence shows that botulinum toxin injections for the treatment of congenital muscular torticollis is safe and effective, with few serious adverse reactions. Further well-designed, larger randomized trials are warranted. Abstract : Supplemental Digital Content is available in the text